Organizational climate and sensitivity to criticism of students in the psychology faculty of a public university in Lima - Velásquez Centeno, Carlos Moisés (2016)
This communication reports the adaptation and relationship between the scale of organizational climate and sensitivity to criticism on 338 students of undergraduate, of which 140 are male and 198 female of the faculty of psychology of public university of Lima. Organizational climate scale was finally restructured into four factors: a) factor 1: negative attitude towards the organization (19 items), b) factor 2: quality of work (8 items), c) factor 3: institutional image (4 items), and d) factor 4: competition authority (6 items); while the scale of sensitivity to criticism maintained its very structure. The results arrogated the lack of relationship between organizational climate and sensitivity to criticism, in the same way sex and age does not make a difference with these.